The Various Systems Of Education With Reference To General And Special Education. - payal (Innovative Research Thoughts, 2016)
As was the case in Western nations, the beginnings of special education in India can be traced back to Christian missionaries and nongovernmental organisations that emphasised a charity model of serving populations such as the visually, hearing, and cognitively impaired. In other words, the situation was very similar to how it was in the West. On the other hand, after India gained its independence in 1947 from Great Britain, the government of India became much more engaged in the delivery of educational, rehabilitative, and social services. As a result, India has been steadily moving toward a paradigm of inclusive education over the course of the previous four decades. This chapter discusses the implementation of such a model in relation to the prevalence and incidence rates of disability in India as well as working within family environments that often involve three to four generations of family members. Specifically, the chapter focuses on the prevalence and incidence rates of disability in India. A high level of poverty, appropriate teacher preparation of special education teachers, a lack of binding national laws concerned with inclusive education, a dual governmental administration for special education services, and citizens' and special education professionals' strong concern about whether or not inclusive education practises can be carried out are all included in the challenges that an inclusive education system faces in India.